Prone Positioning in Spontaneously Breathing Subjects With Moderate or Severe ARDS During Invasive Ventilation. - Wiart, Adil; Castanares-Zapatero, Diego; Wittebole, Xavier; Maerckx, Guillaume; David, Guillaume; Laterre, Pierre-Francois; Gerard, Ludovic (Respiratory Care, 2021)
BACKGROUND: Prone positioning (PP) during invasive mechanical ventilation improves outcomes of patients with severe ARDS. Recent studies suggest that PP in spontaneously breathing, nonintubated patients with acute respiratory failure is well tolerated and improves oxygenation. However, little is known regarding patient triggered ventilation in intubated patients with ARDS undergoing PP. We conducted a retrospective review of our experience with placing patients in the prone position in 2 cohorts of subjects with moderate and severe ARDS (ie, one cohort with ARDS related to COVID-19, the other with ARDS unrelated to COVID-19), many of whom were receiving pressure support ventilation (PSV). METHODS: We conducted a retrospective analysis in a single 22-bed mixed ICU. The subjects included in the analysis were ≥ 18 y old, met the Berlin definition for moderate or severe ARDS (whether related COVID-19 or not), and underwent PP during invasive ventilation. RESULTS: 39 subjects were included in the analysis: 20 subjects had ARDS related to COVID-19, while 19 had ARDS related to other etiologies. A total of 113 PP episodes were analyzed: 84 during PSV and 29 during volume control continuous mandatory ventilation. PP during PSV was well tolerated and was effective in improving arterial oxygenation (ie, an increase of median PaO2 /FIO2 from 100 mm Hg [interquartile range 75-120] before PP to 135 mm Hg [interquartile range 111-161] at the end of the PP session, P < .0001). No significant difference between continuous mandatory ventilation and PSV was noted regarding arterial oxygenation during PP. Compared with continuous mandatory ventilation mode, PP during PSV was associated with a significant decrease in the use of neuromuscular blocking agents (4% vs 69% of subjects, P < .001), while sedative requirements remained unchanged. CONCLUSIONS: In a retrospective analysis of consecutive intubated subjects with moderate or severe ARDS, related or not to COVID-19, spontaneous breathing during PP was well tolerated and achieved significant improvement in arterial oxygenation.